1991
DOI: 10.1093/bja/66.6.719
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Regional Analgesia of the Hand

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(3) suggested that good analgesia for hand surgery could be obtained with lower doses of lignocaine than those used for intravenous regional anaesthesia (IVRA). Mter reporting a succesful case (4), we conducted a controlled study comparing IARA with IVRA, using half intravenous dose of lignocaine for intra-arterial injection. This study showed no significant differences between onset, regression and quality of analgesia, failure rate and patients' acceptance (5).…”
mentioning
confidence: 99%
“…(3) suggested that good analgesia for hand surgery could be obtained with lower doses of lignocaine than those used for intravenous regional anaesthesia (IVRA). Mter reporting a succesful case (4), we conducted a controlled study comparing IARA with IVRA, using half intravenous dose of lignocaine for intra-arterial injection. This study showed no significant differences between onset, regression and quality of analgesia, failure rate and patients' acceptance (5).…”
mentioning
confidence: 99%